L'apprentissage de comportements de conduite sécuritaires : quelles modalités pédagogiques en formation ? - Christine Poplimont; Maéva Duchène (Université de Provence, 2013)
This research consists in analyzing the effect of some pedagogical methods recommended in the EU-project GADGET report (Siegrist, 1999) on the reach of the superior levels of Keskinen's structure of goals in driver training. Following its conclusions, driver training must target a better self-knowledge (self-assessment, awareness of one's goals for life and skills for living) so as to enter into an identity construction process (change values, goals) leading to the adoption of new safety driving behaviors. Self-knowledge appears to be the releasing factor of the identity construction process whereas behavior change is its finality. Given the importance of social interactions, especially pedagogical relationship and group dynamics in teaching modalities used in the university driving teachers and instructors training course, a university course that complies with the EU-project GADGET report (Siegrist, 1999) recommendations, our research studies the impact social interactions in training groups have on the identity construction of students. First, we start by analyzing the effects group dynamics and pedagogical relationship have on the subject at an individual level. Secondly, following the identity construction process that has been released, we describe a mimetic process leading to learning new behaviors: these two pedagogical modalities promote learning social skills through mimesis.